EFFECT OF ASSET STRUCTURE AND CAPITAL STRUCTURE ON PROFITABILITY: Empirical Study of Companies in the Consumer Goods Industry Sector, Household Appliances Sub-Sector, 2014-2020 - Priatna, Husaeri; Anggraini, Iseu; Ananda, Ira (Universitas Indonesia Membangun, 2023)
This study analyzes the influence of Asset Structure and Capital Structure on Profitability (Empirical Study of Manufacturing Companies in the Consumer Goods Industry Sector, Household Appliances Sub-Sector Listed on the IDX for the 2014 – 2020 period). The analytical method used is multiple linear regression analysis to determine the effect of two independent variables on one dependent variable. The population in this study are financial reports published by Manufacturing Companies in the Consumer Goods Industry Sector, Household Appliances Sub-Sector listed on the IDX, and samples were taken for 7 years, namely from 2014 to 2020 using the Financial Position Report and Profit and Loss Report to obtain data. Asset Structure, Capital Structure, and Profitability. Based on the results of the study that partially Asset Structure has a positive and significant effect on Profitability, Capital Structure has a negative and insignificant effect on Profitability, and simultaneously Asset Structure and Capital Structure have a positive and significant effect on Profitability. The Coefficient of Determination results of 40.5% and the remaining 59.5% are other variables that also influence Profitability but are not examined. Profitability in this study using Return on Equity (ROE).